Terrorism and Right-Wing Extremism: History and Comparative Definitions - Antwi-Boasiako, Kwame Badu; Hill, Caleb Grant (Political Preferences, 2020)
Recent narratives on terrorism have focused on the definitions. Terrorism is not a new phenomenon, but the problem resides in its definition and who is defining it. Conceptualizing terrorism depends on which framework one utilizes. The use of different lenses to define the term has contributed to the lack of global acceptance of what constitutes terrorism, hence the difficulty of gathering data for analysis. It is also a conundrum when powerful nations legitimize their terrorist activities against weaker ones. This, unfortunately, has led to the subjectiveness of every attempt in the literature to objectively provide a globally acceptable definition. Using meta-analysis as the methodological approach for the study a number of definitions were scrutinised. This article provides a brief examination of the intersection between right-wing terrorism and ethnic nationalism, and how accelerationism escalates ideology into violence. The paper compares two acts of violence, one traditionally viewed as terrorism and the other labelled solely as a mass shooting. It concludes with a comparative analysis of the definitions provided, utilizing a case study to examine how labels of a terrorist or a freedom fighter impact on one’s view of a group’s motivation. This is pertinent when analysing ideologically motivated violence.